A prospective study of adolescents' body dysmorphic symptoms: Peer victimization and the direct and protective roles of emotion regulation and mindfulness. (March 2018) - Lavell, Cassie H.; Webb, Haley J.; Zimmer-Gembeck, Melanie J.; Farrell, Lara J.
Highlights: In adolescents, appearance victimization associated with higher BDD symptoms. Emotion regulation strategies and clarity associated with fewer BDD symptoms. Mindfulness components awareness and nonjudging associated with fewer BDD symptoms. Mindfulness component observing associated with higher BDD symptoms. Awareness and observing moderated appearance victimization and BDD symptoms. Abstract: In this study, we examined whether peer appearance-related victimization was associated with adolescents' increasing body dysmorphic disorder (BDD) symptoms over 12 months. Also, given emotion regulation and mindfulness have been associated with less body dissatisfaction, we expected that they would protect against the negative impact of peer victimization on BDD symptoms. Participants were 367 Australian adolescents ( M age  = 13 years). In multiple regressions, two aspects of emotion regulation, strategies and clarity, and two components of mindfulness, acting with awareness and being non-judgmental, were uniquely associated with fewer BDD symptoms at T2 relative to T1. There was evidence that one mindfulness component, observing, was a risk factor for more BDD symptoms. Further, acting with awareness and observing moderated the prospective relationship between victimization and BDD symptoms; low acting with awareness and high observing were risks for symptoms regardless of victimization, whereas high acting with awareness and low observing appeared protective of BDD symptoms, but only for adolescents who reported lower victimization.